The secret cave : discovering Lascaux - McCully, Emily Arnold (Farrar Straus Giroux, 2010)
"Jacques, Jojo, Simon, and Marcel were looking for buried treasure when they explored a cave in the south of France in 1940. But the treasure inside was not what they expected, and in fact far more valuable: the walls were covered with stunning prehistoric paintings and engravings, preserved within the sealed cave for over 17,000 years. This is the true story of the boys who discovered the cave of Lascaux, bringing to the modern world powerful examples of the very beginning of art."--Amazon.com.